Atypical Presentation of Atypical Teratoid Rhabdoid Tumor in a Child. (27th May 2013) - Udaka, Y. T.; Shayan, K.; Chuang, N. A.; Crawford, J. R.
Abstract : Atypical Teratoid Rhabdoid Tumor (ATRT) is a rare malignant intracranial neoplasm more commonly diagnosed in young children. The authors report the case of an 11-year-old boy with a long standing history of slowly progressive weight loss, fatigue, and weakness over 1.5 years whose magnetic resonance imaging revealed a large heterogeneous enhancing dorsally exophytic lower brainstem mass. Examination revealed extreme cachexia, gaze-evoked nystagmus, dysphagia, dysarthria, bilateral dysmetria, and global weakness without ambulation. The protracted history and neuroimaging features were most suggestive of a low grade glioma. However, pathology revealed a hypercellular tumor with large hyperchromatic nucleoli and loss of INI-1 staining on immunohistochemistry consistent with a diagnosis of an ATRT. The child died shortly after surgery due to complications from his brainstem infiltrative disease. This case illustrates the diverse presentation of ATRT in childhood that can clinically and radiographically mimic that of low grade glioma.